2003
DOI: 10.1001/archinte.163.3.286
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Celiac Disease in At-Risk and Not-At-Risk Groups in the United States

Abstract: Our results suggest that CD occurs frequently not only in patients with gastrointestinal symptoms, but also in first- and second-degree relatives and patients with numerous common disorders even in the absence of gastrointestinal symptoms. The prevalence of CD in symptomatic patients and not-at-risk subjects was similar to that reported in Europe. Celiac disease appears to be a more common but neglected disorder than has generally been recognized in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

44
1,027
5
81

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 1,551 publications
(1,166 citation statements)
references
References 34 publications
(36 reference statements)
44
1,027
5
81
Order By: Relevance
“…This may have resulted in an overestimate of the prevalence of celiac disease in some patient groups however rates of celiac disease in different patient cohorts are similar to previous case finding studies reported in the literature. [27][28][29] Furthermore this increased prevalence did allow us to accrue significant numbers of patients with USCD to allow for effective comparison of patient phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…This may have resulted in an overestimate of the prevalence of celiac disease in some patient groups however rates of celiac disease in different patient cohorts are similar to previous case finding studies reported in the literature. [27][28][29] Furthermore this increased prevalence did allow us to accrue significant numbers of patients with USCD to allow for effective comparison of patient phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…25 This statistic is the ratio of observed over expected CD prevalence, assuming a general population risk of 1:133. 3 The change in scores from baseline to follow-up was summarized as mean change and 95 percent CIs. A p<0.05 was considered significant.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] Familial aggregation is common: a large American study that recruited relatives during CD-support group meetings identified ∼5% of first-degree relatives with CD. 3 This is less than in Europe and may reflect different case selection, recruitment, and testing. The prevalence is higher in relatives of affected sibling pairs (17.2%), 7,8 monozygotic twins (75%) and human leukocyte antigen (HLA)-identical siblings (40%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have indicated that the prevalence of diagnosed celiac disease has increased from 1 per 4,800 to 1 per 2,000 in the United States [4]. This probably still greatly underestimates the true prevalence as judged by population-based screening studies [5]. Still considered a rare clinical entity in this country, potential celiac disease is often ignored by clinicians, despite the fact that the condition predominantly affects Caucasians, who comprise over 190 million residents of the United States.…”
Section: Introductionmentioning
confidence: 98%